Persistence of benthiocarb in soil: influence of ultraviolet and sunlight - Aktar, Md. Wasim; Paramasivam, M.; Sengupta, Dwaipayan (Orbital: The Electronic Journal of Chemistry, 2008)
Persistence of benthiocarb in soil as affected by UV and sunlight exposure was studied. Treated soil was placed in petri plate, brought to field capacity moisture and then exposed to UV and sunlight. Residues of benthiocarb in soil dissipated with half lives of 2.10, 11.85 and 43.63 days under UV, sunlight and dark condition, respectively. Soil samples kept under dark showed the slowest dissipation. Further, benthiocarb residues dissipated quickly under UV light as compared to sunlight. Exposure of thin film of benthiocarb confirmed that it is photo labile and dissipated very fast with half life of 1.16 and 1.77 days following exposure to UV and sunlight, respectively. The study revealed that UV component of sunlight is an important factor for benthiocarb dissipation.